MKRN3 regulates the epigenetic switch of mammalian puberty via ubiquitination of MBD3. Issue 3 (14th February 2020) - Li, Chuanyin; Lu, Wenli; Yang, Liguang; Li, Zhengwei; Zhou, Xiaoyi; Guo, Rong; Wang, Junqi; Wu, Zhebao; Dong, Zhiya; Ning, Guang; Shi, Yujiang; Gu, Yinmin; et al.
Abstract: Central precocious puberty (CPP) refers to a human syndrome of early puberty initiation with characteristic increase in hypothalamic production and release of gonadotropin-releasing hormone (GnRH). Previously, loss-of-function mutations in human MKRN3, encoding a putative E3 ubiquitin ligase, were found to contribute to about 30% of cases of familial CPP. MKRN3 was thereby suggested to serve as a 'brake' of mammalian puberty onset, but the underlying mechanisms remain as yet unknown. Here, we report that genetic ablation of Mkrn3 did accelerate mouse puberty onset with increased production of hypothalamic GnRH1. MKRN3 interacts with and ubiquitinates MBD3, which epigenetically silences GNRH1 through disrupting the MBD3 binding to the GNRH1 promoter and recruitment of DNA demethylase TET2. Our findings have thus delineated a molecular mechanism through which the MKRN3–MBD3 axis controls the epigenetic switch in the onset of mammalian puberty.